Power of industrial court to award costs in claims for dismissal without just cause or excuse - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2019)
The issue that forms the basis of this article is whether the costs incurred by either party in bringing or defending their claims for unfair dismissal would be recoverable.